Ice, Ice, Baby - Michael Smith; Thomas Noeller (Association of American Medical Colleges, 2011)
Abstract This is a high-fidelity human patient simulation involving a severely hypothermic patient requiring invasive measures to rewarm the patient's core temperature. Altered physiology, along with medical and traumatic scenarios that put the patient at risk for severe hypothermia, is also addressed. This severely ill, critically hypothermic patient requires the learner to go through a differential diagnosis of hypothermia causes (trauma/medical) along with understanding the altered physiology (and altered advanced cardiovascular life support recommendations) when a patient is hypothermic. In addition, invasive measures are required to warm the patient. Anecdotally, these measures are often quoted, but in practice, they are sometimes difficult to perform (thereby becoming a system issue as well). The simulation lasts 45-60 minutes. We rotated approximately 39 residents through the scenario. One faculty member and programmer were required per scenario. Each scenario was then video debriefed. We found that residents had knee-jerk reactions to hearing about what to do in a critically ill hypothermic patient, but actually putting this into practice proved much more difficult. Also, because hypothermic (and hyperthermic) patients can provoke system strains as they tend to be resource intensive.